The effect of women's socio-demographic variables on their empowerment - Nikkhah, Hedayat Allah; Redzuan, Ma'rof; Abu Samah, Asnarulkhadi (Marsland Press, 2010)
Social scientists and development agencies have long been interested in the conditions that empower women. Since the empowerment could give women freedom of choice, equal access to domestic and community resources, opportunities and powers, thus, empowerment of women and the improvement of their status, particularly in respect of education, health and economic opportunities (occupation), are highly important ends in themselves. However, there are many factors which stop women benefiting from such development and contribute to women’s powerlessness such as inequality in economic opportunity, lack of knowledge, skills, and lack of access to education. This study elucidates the relationship between socio-demographic variable of women and their empowerment in Shiraz, Iran. Indeed, this study discovered the effect of respondents’ background i.e., age, education, occupation, family income and marital status on their empowerment. Data was collected from 195 women who participated in empowerment process which organized by NGOs in the whole city of Shiraz. The result of study showed that among the socio-demographic variables, only education and marital status had effect on empowerment. It can be concluded that access to education and knowledge play an important role increasing women empowerment. The result of study also showed that the divorced women have high level of empowerment compare to married and widow women. This is might due to that married women couldn’t get their husband permission to participate in empowerment process.